A new form of the calibration curve in radiochromic dosimetry. Properties and results. Issue 7 (24th June 2016) - Tamponi, Matteo; Bona, Rossana; Poggiu, Angela; Marini, Piergiorgio
Abstract : Purpose: This work describes a new form of the calibration curve for radiochromic dosimetry that depends on one fit parameter. Some results are reported to show that the new curve performs as well as those previously used and, more importantly, significantly reduces the dependence on the lot of films, the film orientation on the scanner, and the time after exposure. Methods: The form of the response curve makes use of the net optical densities ratio against the dose and has been studied by means of the Beer–Lambert law and a simple modeling of the film. The new calibration curve has been applied to EBT3 films exposed at 6 and 15 MV energy beams of linear accelerators and read‐out in transmission mode by means of a flatbed color scanner. Its performance has been compared to that of two established forms of the calibration curve, which use the optical density and the net optical density against the dose. Four series of measurements with four lots of EBT3 films were used to evaluate the precision, accuracy, and dependence on the time after exposure, orientation on the scanner and lot of films. Results: The new calibration curve is roughly subject to the same dose uncertainty, about 2% (1 standard deviation), and has the same accuracy, about 1.5% (dose values between 50 and 450 cGy), as the other calibration curves when films of the same lot are used. Moreover, the new calibration curve, albeit obtained from only one lot of film, shows a good agreement with experimental data from all other lots of EBT3 films used, with an accuracy of about 2% and a relative dose precision of 2.4% (1 standard deviation). The agreement also holds for changes of the film orientation and of the time after exposure. Conclusions: The dose accuracy of this new form of the calibration curve is always equal to or better than those obtained from the two types of curves previously used. The use of the net optical densities ratio considerably reduces the dependence on the lot of films, the landscape/portrait orientation, and the time after exposure. This form of the calibration curve could become even more useful with new optical digital devices using monochromatic light.